2010
DOI: 10.1103/physrevb.82.125104
|View full text |Cite
|
Sign up to set email alerts
|

First-principles investigation on redox properties ofM-dopedCeO2(M=

Abstract: The effects of M ͑M =Mn,Pr,Sn,Zr͒ doping on the redox thermodynamics of CeO 2 have been investigated using first-principles density-functional theory calculations with the on-site Coulomb interaction taken into account. Two different mechanisms for the O-vacancy formation in doped CeO 2 have been clarified. Compared with the case of pure CeO 2 , the decrease in the O-vacancy formation energy for the Zr-doped CeO 2 is mostly caused by the structural distortion, whereas the decrease for Mn-, Pr-, or Sn-doped CeO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(58 citation statements)
references
References 67 publications
8
50
0
Order By: Relevance
“…For the Mn dopant in ceria, a U-correction for the Mn d-states must be added to correctly represent the electronic structure of Mn-doped CeO 2 [2,3,13,[17][18][19]34]. A U-value of 4 eV on the d-states of Mn has been confirmed to properly represent the Mn oxidation state under reducing conditions, in agreement with both x-ray adsorption near edge spectroscopy (XANES) and DFT results using the hybrid functional HSE06 [2,3].…”
Section: Electronic Structure Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…For the Mn dopant in ceria, a U-correction for the Mn d-states must be added to correctly represent the electronic structure of Mn-doped CeO 2 [2,3,13,[17][18][19]34]. A U-value of 4 eV on the d-states of Mn has been confirmed to properly represent the Mn oxidation state under reducing conditions, in agreement with both x-ray adsorption near edge spectroscopy (XANES) and DFT results using the hybrid functional HSE06 [2,3].…”
Section: Electronic Structure Methodsmentioning
confidence: 69%
“…Compared with other oxides and metals that can be mixed with CeO 2 , MnO x can increase the stability of the catalyst [6], and is less expensive than other metals (Ag, Au, Pt, Pd) that can increase the activity of ceria [13][14][15][16]. Cen et al [17], Gupta et al [18], and Tang et al [19] all showed that the addition of Mn to the ceria surface increases the reducibility of the surface. Mn will dope into the lattice of ceria with oxygen vacancies present and also increases the reducibility and catalytic activity of the surface [3,13].…”
Section: Introductionmentioning
confidence: 95%
“…Whereas, in the case of aliovalent dopants the decrease in the defect formation energy is due to the structural distortion, and also due to the electronic modifications, which result in the generation of extra oxygen vacancies [24,25]. On the other hand, in aliovalent metal ions, bivalent dopants like Ca 2+ are not preferable.…”
Section: Introductionmentioning
confidence: 94%
“…Doping of an aliovalent cation in place of Ce leads to the reduction and formation of oxygen vacancies 19,20,21 . On the introduction of a dopant, oxygen vacancies are formed by both structural and electronic modifications in ceria 22,23 . An increase in the dopant concentration results into a greater likelihood of vacancy clustering 24 .…”
Section: Introductionmentioning
confidence: 99%